Making friends, volume 3 ebook Third time's a charm. - Gudsnuk, Kristen (Making Friends, 2021)
Dany's sketchbook is at it again, but this time it's not Dany's doing! Dany and Madison are living a new reality. Rather than best friends, the pair now believe they are twins — and that isn't the only part of their lives that has been completely rewritten. Their mom is a novelist, their dad is a rock star, and Dany has suddenly become a diligent student. Things. Aren't. Adding. Up. Dany and Madison start sleuthing and discover that someone has drastically altered the universe! Can the pair put things back the way they were, or is this magic beyond their control?